AN AWARENESS OF WHAT IS MISSING: VOYEURISM AND THE REMEDIATION OF TRANSCENDENCE IN ARNOLD STADLER'S SEHNSUCHT AND SALVATORE. (July 2014) - Fuchs, Anne
ABSTRACT Engaging with the current debate on secularism and the new religious turn in contemporary German literature, my paper explores the interdependence of voyeurism and transcendence in Arnold Stadler's Sehnsucht. Versuch über das erste Mal and Salvatore. Stadler's works articulate a poetics of longing that encompasses both the carnal and the transcendental. While the first part analyses the enmeshing of the protagonist's sexually charged scopophilic curiosity with his desire for transcendence in Sehnsucht, the second part analyses the sublimation and remediation of voyeurism in Salvatore. Here Stadler draws on Pasolini's film The Gospel According to Matthew and on Caravaggio's The Calling of St Matthew to set in train a complex circuit of intermedial and intertextual exchange. The conversion of Biblical text into film and Renaissance art and the reconversion of visual images into fictional text emphatically appeals to the reader's imaginative participation for the recovery of transcendence. Salvatore envisages a model of participatory discipleship that aims to unleash an aesthetically engendered presence in the recipient. Faith is no longer a matter of doctrinal teaching but an intermedial experience based on the persuasiveness of aesthetic images.